MOE and MOR assessment of in service and dismantled old structural timber. (15th October 2016) - Cavalli, Alberto; Bevilacqua, Lorella; Capecchi, Gianluca; Cibecchini, Daniele; Fioravanti, Marco; Goli, Giacomo; Togni, Marco; Uzielli, Luca
Highlights: 81 old timber members tested in bending for the MOE/MOR calculation. MOE/MOR assessment based on NDT. Large sample of old structural timber tested. On site and after dismantling old structural timber assessment. Abstract: 81 timber beams (14 of Spruce and 67 of Silver fir) were salvaged from different historical buildings. All the timber were visually graded, dynamically (vibration and acoustic methods were used) and statically (four point bending test) tested, to calculate the actual MOE/MOR. The results of the visual strength grading and dynamic tests were combined, in order to predict MOE and MOR on-site, or on reclaimed timber after their dismantling. For salvaged timbers, comparable results to those reported in literature for new solid timbers were obtained on MOE/MOR prediction, combining longitudinal vibration tests and wane extension (r 2 = 0.71 and 0.43 for MOE and MOR prediction respectively). Within this research, alternative simplified methods, for the MOE/MOR prediction, which are based on the stress wave velocity and wane extension, applicable on site, were proposed (r 2 = 0.57 and 0.29 for MOE and MOR prediction respectively). Since the results were obtained by testing a sample with large variability, adopting some simplifications, they can be used as a starting point for the assessment of MOE/MOR of timber directly on-site, or to evaluate the mechanical properties of reclaimed timber after their dismantling, to assess their potential reuse in timber structures.